2008
DOI: 10.1080/17453670710015265
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vacuum‐formed removable rigid dressing with conventional rigid dressing after transtibial amputation

Abstract: The vacuum-formed rigid dressing appears to give results similar to those of the conventional rigid dressing regarding time to prosthetic fitting and patient's function with prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In a study by Johannesson et al 18 (n = 27), a ‘vacuum-manufactured RRD’ was compared with a conventional RRD. The study was of sufficient methodological quality, and similar results were found for the vacuum-manufactured RRD compared with the conventional RRD with respect to time to prosthetic fitting, wound healing and function at 3 months.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…In a study by Johannesson et al 18 (n = 27), a ‘vacuum-manufactured RRD’ was compared with a conventional RRD. The study was of sufficient methodological quality, and similar results were found for the vacuum-manufactured RRD compared with the conventional RRD with respect to time to prosthetic fitting, wound healing and function at 3 months.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…Following article synthesis, the following empirical evidence statements were made with regard to postoperative care: 1. In persons with acute TTA from vascular disease, vacuum-formed dressings are comparably effective at preparing the limb for prosthetic use and ambulation as measured by the number of days from amputation to prosthetic fitting, wound healing rate, and mobility compared with conventional Plaster of Paris dressings [41]. 2.…”
Section: Postoperative Carementioning
confidence: 99%
“…The addition of vacuum to postoperative dressings represents a newer application of vacuum technology as well as a novel type of acute dressing option. In nonambulatory acute, postoperative TTAs, Johannesson et al report that vacuum-formed RRDs were not different in time from amputation to prosthetic fitting, wound healing rate, and mobility compared with conventional plaster RRDs [41].…”
Section: Postoperative Carementioning
confidence: 99%
See 1 more Smart Citation
“…Three months postamputation, the researchers measured each patient with the Locomotor Capability Index and the Timed “Up and Go” test and found both groups performed equally. The authors concluded the RRD appears to give results similar to those of conventional RDs regarding time to prosthetic fitting and patient's function with prosthesis [26].…”
Section: Assessment Of the Literaturementioning
confidence: 80%